ChemInform Abstract: Tailoring the Structures and Compositions of One‐Dimensional Organic Nanomaterials Towards Chemical Sensing Applications. Issue 16 (22nd April 2014) - Cui, Qiu Hong; Zhao, Yong Sheng; Yao, Jiannian
Abstract Review: [34 refs.